Converter with Synchronous Rectifiers for Electroplating - Hurtuk, Peter; Priecinsky, Martin; Kondelova, Anna (Communications - Scientific letters of the University of Zilina, 2011)
This paper presents the requirements for resources for electroplating processes, principles of the synchronous rectifier and its control. It describes simulation and experimental verification of the synchronous rectifier, compares the efficiency of switching power supply using a synchronous rectifier and a diode rectifier, where body diode of MOSFET transistor is used for rectification. Finally the paper brings thermal images of synchronous rectifier transistors.